1996
DOI: 10.1073/pnas.93.17.9015
|View full text |Cite
|
Sign up to set email alerts
|

Induction of insulin and islet amyloid polypeptide production in pancreatic islet glucagonoma cells by insulin promoter factor 1.

Abstract: Insulin promoter factor 1 (IPF1), a member of the homeodomain protein family, serves an early role in pancreas formation, as evidenced by the lack of pancreas formation in mice carrying a targeted disruption of the IPF1 gene [Jonsson, J., Carlsson, L., Edlund, T. & Edlund, H. (1994) Nature (London) 371,[606][607][608][609]. In adults, IPF1 expression is restricted to the a-cells in the islets of Langerhans. We report here that IPF1 induces expression of a subset of 8-cell-specific genes (insulin and islet am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
89
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 46 publications
6
89
0
Order By: Relevance
“…The MSL AN697C1 subclone gave rise to two derived cell lines, namely the glucagon-secreting AN-glu, and after stable transfection with the transcription factor pancreatic duodenal homeobox factor-1, the insulin secreting ANins (27). Despite having similar rates of NO synthesis, we found that the AN-ins cells were more susceptible to apoptosis elicited by IL-1␤.…”
mentioning
confidence: 49%
“…The MSL AN697C1 subclone gave rise to two derived cell lines, namely the glucagon-secreting AN-glu, and after stable transfection with the transcription factor pancreatic duodenal homeobox factor-1, the insulin secreting ANins (27). Despite having similar rates of NO synthesis, we found that the AN-ins cells were more susceptible to apoptosis elicited by IL-1␤.…”
mentioning
confidence: 49%
“…The in vivo study on mice with ␤-cell-specific deletion of PDX-1 (36) and our in vitro work on INS-1 cells expressing DN-Pdx-1 (31) indicate that PDX-1 promotes the ␤-cell phenotype by maintaining the expression of ␤-cell-specific genes while suppressing glucagon levels. Suppression of glucagon expression by PDX-1 requires synergism with other ␤-cell-specific transcription factors because ectopic expression of PDX-1 in glucagonoma cells failed to eliminate glucagon (40). We also showed that maximum induction of Brain-4, an ␣-cell-specific transcription factor, initiated detectable levels of glucagon but did not attenuate the expression of ␤-cell-specific genes in INS-1 cells (31).…”
Section: Experimental Models Of Modymentioning
confidence: 62%
“…A similar expression profile results from dominant negative suppression of Pdx1 in INS1 beta cells [85]. In vitro binding and transient transfection studies suggest that Pdx1 interacts directly with the 5′ flanking regions of these four genes [86,87,88,89], while ChIP experiments have confirmed that Pdx1 binds in vivo to the insulin and IAPP genes in cultured beta cell lines [90,91].…”
Section: Neurogenin 3 Orchestrates a Network That Drives Endocrine DImentioning
confidence: 65%